The Effect Of Land Use Conversion On Groundwater Quality In Dukuhwaluh Village Kembaran Subdistrict Banyumas Regency - Rahayu, Wiwit Sayekti; Suwarsito, Suwarsito; Sarjanti, Esti (Prosiding University Research Colloquium, 2021)
Groundwater is the main source of water that is used to meet basic human needs. This study aims to determine the effect of land conversion on groundwater quality in Dukuhwaluh Village, Kembaran District, Banyumas Regency. This study uses a survey method. The population in this study is groundwater. The sampling technique of this research is purposive area sampling with the criteria of settlement density and distance between wells. Sampling was carried out at 6 sample points. The data used in this study are primary data including land use data in 2020 and groundwater quality data. Secondary data includes data on area, land use, livelihoods, and education level. Primary data collection through field observations in the form of land use collected for land use in 2020 and groundwater quality data for temperature, pH, TDS parameters as well as laboratory tests for ammonia, nitrate and e-colli bacteria parameters. Groundwater quality analysis was carried out using the matching data method according to drinking water quality standards. The results showed that in the village of Dukuhwaluh there was a conversion of an area of 14.235% of land into residential land. This can affect the quality of groundwater in the presence of inappropriate ammonia and e-colli bacteria.